PERUBAHAN PENUTUPAN LAHAN BERDASARKAN ANALISIS CITRA DIGITAL DI DAERAH ALIRAN SUNGAI MAHAKAM - Prasetyo, Mohammad Aji; Mandang, Idris; Mubarrok, Saat (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
This study aims to analyze the land cover in the Mahakam watershed, East Kalimantan in years of 2003 and 2015 by using data satellite LANDSAT ETM+ image and LANDSAT OLI / TIRS with spatial resolution 30 m. The method used is the initial processing of the image, visual image interpretation, field observations, the determination of sample area, supervised classification using the maximum likelihood method, analysis of accuracy test, reclassification, and analysis of land cover change. Land cover of Mahakam watershed can be classified into 5 type of land cover, namely vegetation, fishpond, settlements, open land and watershed. In 2003, the vegetation area in the Mahakam watershed reached 1.135.629 ha and up to 1.139.318 ha or about 0,53 % in 2015. At the same time, the class of settlement increased from 11.823 ha in 2003 to 79.303 ha in 2015. The land cover of watershed also increased by 6,78 %, from 110.969 ha increasing to 222.560 ha. Open land area has decreased of around 9,77 % or 160.807 ha converted to watershed, vegetation, and settlement.Type of land cover mining has decreased in the period 2003-2015, amounting to 29.177 ha or 1,77 %. Which is converted to vegetation and open land. It shows that land cover change in Mahakam watershed is dominated by open land that is used by the community as settlements, plantations and others.